Kdo tu mluvil o vítězství? Osm cvičení ve filosofické rezignaci - Matějčková, Tereza (Myšlení současnosti, 2022)
Traditional cultures have exercises which teach people discipline. Even modern philosophers, Hegel, Nietzsche and Kierkegaard paid special attention to striving for spirituality, although outside religious frameworks. However, if we are to grow, we should relax the relationship to ourselves. Hence the notion of resignation. A resigned will is not weak, it is able to resist itself and others. Such resignation is a man's defense against becoming a mere element in a sequence of events. Art, philosophy, and mainly freedom all lie in the ability to create distance. In her most recent book, Tereza Matějčková offers more than a history of a notion or a thematic reading of the legacy of respected thinkers - a fresh view of a newly asked question of self-acceptance and growth.